Comprehensive disease survey of sunflower in Southern Karnataka: COMPREHENSIVE DISEASE SURVEY OF SUNFLOWER IN SOUTHERN KARNATAKA - B S CHETHANA; ARJUMANBANU; C P MANJULA; K KARUNA; SRINIVASA REDDY (Journal of Oilseeds Research, 2026)
Sunflower (Helianthus annuus L.) is an important oilseed crop in Karnataka, India, cultivated mainly under rainfed conditions. In recent years, the crop has been increasingly affected by major diseases, resulting in considerable yield losses. To sustain productivity, it is imperative to gather information on disease distribution across Karnataka's major sunflower-growing regions. The present study aimed to document the occurrence and distribution of diseases from kharif 2015-2016 to 2024-2025 in the Chamarajanagar and Chitradurga districts of southern Karnataka. The results revealed that Alternaria leaf blight, powdery mildew, and sunflower necrosis disease were the most prevalent and economically important diseases during the ten-year study period. The highest disease severity of Alternaria leaf blight (60-90%) and powdery mildew (65%) was recorded in Chamarajanagar and Chitradurga, respectively, during 2024, whereas the highest incidence of sunflower necrosis disease (50-90%) was observed in Chitradurga during 2022. Diseases such as downy mildew (7-8%), Rhizopus head rot (7-20%), wilt (5-10%), and rust (8-10%) occurred sporadically. Rainfall-dependent cultivation under rainfed conditions emerged as a major factor contributing to the spatial and temporal variation in disease intensity. The findings indicate a shifting disease scenario in sunflower, driven by climatic variability, rainfall-dependent cultivation, and the low adoption of recommended plant protection practices. Therefore, continuous disease surveillance, promotion of resistant hybrids, and adoption of region-specific integrated disease management strategies are essential to mitigate yield losses and ensure sustainable sunflower production.